Colonoscopy in patients without sedation: an experience from Nepal (Health Renaissance, 2012)
Background: Colonoscopy is considered a painful procedure requiring routine intravenous sedation, however there are number of potential advantages to performing colonoscopy without sedation. Objective: To determine the effect of unsedated colonoscopy on the success rate of caecal intubation. Methods: All charts of patients who had unsedated colonoscopy from September 2010 to August 2011 were reviewed. Patient characteristics including age, gender, and mode of presentation were collected. The reasons for incomplete colonoscopy and sites reached were recorded. Results: During the study period, 127 examinations were performed without sedation. The mean age of the patients was 41.9 years with 79% males. The most common indication for performing colonoscopy was irritable bowel syndrome and the predominant endoscopic finding was colitis other than inflammatory bowel disease. The completion rate was 80.3%. Conclusion: In this study, sedation probably affects the overall success rate of cecal intubation. But unsedated colonoscopy can be used in resource poor settings to minimize direct and indirect costs of colonoscopy. DOI: http://dx.doi.org/10.3126/hren.v10i1.6003 HREN 2012; 10(1): 27-29